A Theoretical Study to Calculate the Radiation Stopping Power for Electrons in Human Tissues - Musaab Imad (Tikrit Journal of Pure Science)
In this research, the radiation stopping power of electrons in some human tissues (adipose tissues, blood, bone compact, bone cortical, brain, eye lens, lung, skin, and testicles) was studied within the energy range from (10 MeV) to (1000 MeV). The study of the energy loss of charged particles through matter is of great importance in medical physics in general and radiotherapy in particular in order to determine the radiation dose in the case of medical tests or treatment and the effect of this dose in the cells adjacent to the target cells and possible damage to the tissues adjacent to the affected tissues. Calculations have been performed using the modified Berger-Seltzer equation (where a new formula was found to calculate the approximate function as a function of the energy of the incident electron using the data matching method and using the Curve Expert program). The radiation stopping power of each of the components of the tissue was found separately, and then the stopping power of the tissue was found using the Bragg rule for compounds. All calculations were performed using the MATLAB program. Comparing the results obtained with the value of the universal code E-Star, it was found that they matched well and that the error rate was less than (1 %).